Critical Reviews of Toni Morrison’s The Bluest Eye and Song of Solomon - Aboud Hammed, Samer Majeed; Haji Mat Said, Seriaznitabinti (International Journal of Psychosocial Rehabilitation, 2019)
This paper attempts to review Toni Morrison’s The Bluest Eye and Song of Solomon from different critical perspectives. The significance of this review is to provide ample evaluation of the novels in various critical contexts that might enable researchers to conceptualize Morrison’s contemporary perception of her people and society in diverse literary styles. In addition, the study tries to open new literary horizons for readers to perceive the precise fictional modes utilized by Morrison to depict reality outside the texts. For this reason, studying Morrison form many perspectives would lead academic researchers to have sufficient knowledge of her influence upon the American literature in particular and world literature in general. As such, the study will find that the selected novels are meticulous replicas of Morrison’s’ writing style as well as her portrayal of reality. Thus, the selected works will be approached by pursuing different critical disciplines, like feminism, racism and psychoanalysis which have been applied to discover various themes in the selected works.